Extracellular Membrane Vesicles and Immune Regulation in the Brain - Pluchino, Stefano; Cossetti, Chiara; Smith, Jayden A.; Iraci, Nunzio; Leonardi, Tommaso; Alfaro-Cervello, Clara (Frontiers in Physiology, 2012)
The brain is characterized by a complex and integrated network of interacting cells in which cell-to-cell communication is critical for proper development and function. Initially considered as an immune privileged site, the brain is now regarded as an immune specialized system. Accumulating evidence reveals the presence of immune components in the brain, as well as extensive bidirectional communication that takes place between the nervous and the immune system both under homeostatic and pathological conditions. In recent years the secretion of extracellular membrane vesicles (EMVs) has been described as a new and evolutionary well-conserved mechanism of cell-to-cell communication, with EMVs influencing the microenvironment through the traffic of bioactive molecules that include proteins and nucleic acids, such as DNA, protein coding and non coding RNAs. Increasing evidence suggests that EMVs are a promising candidate to study cross-boundary cell-to-cell communication pathways. Herein we review the role of EMVs secreted by neural cells in modulating the immune response(s) within the brain under physiological and pathological circumstances.